Rural livelihoods and poverty reduction policies - Ellis, Frank; Freeman, H. Ade (Routledge studies in development economics ;, 2005)
This important new collection of contributions brings together current thinking on poverty reduction and rural livelihoods in developing countries. As well as leading economists in the field, there are a number of local contributors.